Strategy create and implement the best strategy for your business. - HBR (Boston Harvard Business School Press, 2005)
Strategic execution drives business success. This book covers strategy from the ground up, explaining what strategy is, how to put together a strategic plan, what tools and resources are necessary to execute it, and how to measure results.
Includes bibliographical references (p. 141-144) and index.
Keywords: Strategic planning